Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-69
|View full text |Cite
|
Sign up to set email alerts
|

Speaker-specific intonational marking of narrow focus in Egyptian Arabic

Abstract: { f cangemi , swehr l e2, s t ef an. baumann, mar t i ne. gr i ce} @ uni-koel n. de, di na. el zar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…The results of the present study indicate that this effect is due to the longer duration of the stressed syllable. As far as peak scaling is concerned, our results confirmed the findings of prior studies on focus in EA with respect to the effect of narrow focus [7,1,8,2,6], however, across a larger number of speakers and tokens. [6] had already shown that for some speakers, peaks are higher in narrow focus than in broad focus (all-new).…”
Section: General Discussion and Conclusionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results of the present study indicate that this effect is due to the longer duration of the stressed syllable. As far as peak scaling is concerned, our results confirmed the findings of prior studies on focus in EA with respect to the effect of narrow focus [7,1,8,2,6], however, across a larger number of speakers and tokens. [6] had already shown that for some speakers, peaks are higher in narrow focus than in broad focus (all-new).…”
Section: General Discussion and Conclusionsupporting
confidence: 89%
“…The random variables are both incorporated in terms of random intercept models. A detailed analysis of speaker-specific strategies, as for instance presented in [6], is left for future work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations